High-safety automobile steering pull rod - FENG SHULIN; DAI JIANYONG (2025)
The high-safety automobile steering pull rod comprises an outer rod body, the two ends of the outer rod body are in threaded connection with fixing bases, the circumferential inner walls of the fixing bases are in threaded connection with threaded rods, one ends of the threaded rods are fixedly connected with ball cups, the outer walls of the threaded rods are sleeved with locking rings, and the locking rings are fixedly connected with the ball cups. The locking ring abuts against the outer wall of one end of the fixing base through a ball cup at one end of the threaded rod, a reinforcing cavity is formed in the outer rod body, and an inner supporting assembly is arranged in the outer rod body. By the adoption of the inner supporting assembly, the outer rod body can be well supported, the strength of the outer rod body is further improved under the condition that the light weight of the outer rod body is guaranteed, and therefore the whole steering pull rod is not prone to cracking or damage fracture after be